Solar tracker development based on a POF bundle and Fresnel lens applied to environment illumination and microalgae cultivation. (1st November 2018) - Allil, Regina Célia; Manchego, Alfredo; Allil, Alexandre; Rodrigues, Igor; Werneck, Arthur; Diaz, Gisel Chenard; Dino, Fabio Toshio; Reyes, Yordanka; Werneck, Marcelo
Highlights: Low cost solar tracker w/ stepper motor, Fresnel lens, plastic optical fiber bundle. Tracker guides solar light to ambience to reduce power consumption for lighting. The new photobioreactor costs less than conventional window-photobioreactor. We demonstrated a higher efficiency in illumination and cultivation. Abstract: Although within the group of countries with the highest solar irradiation index in the world, Brazil still underuses its natural power. Brazil's hydropower energy today makes up 68, 5% of the total energy produced, in contrast however, photovoltaic energy production is still only 0.01%. As an effort to open up new frontiers for solar energy uses, the main objective of this project was to use solar energy in form of light to reduce the power consumption required for continuously lighting any kind of environment as well as to propose a new technology for illuminating a conventional window-type photobioreactor (PBR) in the cultivation of microalgae for biofuel production in order to reduce their associated costs. The system is composed by a solar tracker, an electromechanical control, a Fresnel lens and a plastic optical fiber (POF) bundle, in which tip the lens concentrates the solar radiation. Therefore, at the other end of the bundle, the POFs can be distributed homogeneously in any local where one wants to illuminate. The solar tracker is able to track the Sun from sunrise to sunset using an algorithm whose function is to calculate the Sun position according to the local time and latitude using an equatorial mount structure. In addition, some sensors are employed for monitoring relevant parameters, for instance, the light intensity inside the POF bundle, the right ascension and declination angles of the tracker and the solar radiation. These parameters can be downloaded in real time through a specially designed mobile application. As application of the solar tracker, two projects were developed and described in this paper: two kinds of solar luminaires for illumination of internal ambiences and a closed photobioreactor by POF illumination, with nontransparent material, free of outside contamination with low cost and the study of the produced biomass through the lipid content. Both applications were compared in performance with their conventional counterparts and, as a conclusion, it is shown that in both cases they can substitute their conventional counterparts with advantages.